Introducing Nightlight: A New FITS Viewer. (17th April 2017) - Muna, Demitri
Abstract: Nightlight is a new desktop application designed to visualize astronomical data. A primary motivation for this program is to apply modern user interface design and advancements to the ubiquitous FITS file. In a more general sense, I wish to demonstrate the usefulness and desirability of employing modern, commercial frameworks for use with scientific code. A general description of the initial version of the program is presented here, as well as future development directions. Nightlight is available athttp://nightlightapp.io .